Patterns of sport participation in Portuguese volleyball players according to expertise level and gender - Coutinho, P.; Mesquita, I.; Fonseca, A. M.; De Martin-Silva, L. (International Journal of Sports Science and Coaching, 2014)
This study aimed to examine the sport participation of 229 Portuguese volleyball players through a previously validated questionnaire within different stages of their development and considering their expertise level and gender. The skilled players differed from the less skilled in having accrued more hours of training throughout all stages. Female players reported less early sport involvement (fewer number of sports practiced and less involvement in team sports and competitions) than males. The early involvement in individual sports by skilled female players seems to be important in their route to expertise, while the later involvement in individual sports by less-skilled male players possibly indicates the need for other motivational sport experiences. These particular findings provide valuable information to guide the designs of Portuguese volleyball players' development considering gender and expertise at the same time. However, additional work is needed to understand to what extent these findings may be system, culture or sport dependent.